The Wiley handbook on the cognitive neuroscience of memory - Addis, Donna Rose, 1977-; Barense, Morgan, 1980-; Duarte, Audrey, 1976- (Hoboken, New Jersey : Wiley-Blackwell, 2015)
"The Wiley Blackwell Handbook on the Cognitive Neuroscience of Memory presents a comprehensive overview of the latest, cutting-edge neuroscience research being done relating to the study of human memory and cognition"--
Explaining modality-specific impairmentsExplaining category-specific patterns of impairment and functional activation; Conclusions and Open Questions; References; Chapter 5 Encoding and Retrieval in Episodic Memory: Insights from fMRI; Introduction; Theoretical Framework; Empirical Findings; Encoding; Positive subsequent memory effects; Negative subsequent memory effects; Retrieval; Content-sensitive recollection effects; Concluding Comments; Acknowledgments; References; Chapter 6 Medial Temporal Lobe Subregional Function in Human Episodic Memory: Insights from High-Resolution fMRI.
Includes index.
Includes bibliographical references at the end of each chapters and index.
Print version record and CIP data provided by publisher.
Keywords: Memory; Cognitive neuroscience; Brain -- Imaging; Memory; Cognitive neuroscience; Memory -- Physiological aspects; Memory; PSYCHOLOGY -- Cognitive Psychology; Brain -- Imaging; Cognitive neuroscience; Memory; Electronic books